The Relation ship between Varicocele and Body Mass Index. - Farhan, Saad D. (Journal of the Faculty of Medicine Baghdad, 2010)
Background:Varicoceles, present in 15% to 20% of men, are the most common abnormal finding among men presenting with infertility, yet controversy exists regarding their etiology. Anecdotal experience suggests that varicoceles are more prevalent in lean men, supporting the "nutcracker" effect of the superior mesenteric artery compressing the left renal vein over the aorta. Materials and methods: A total of 206 males with varicocele attending the urological out patient clinic were evaluated from their physical screening examinations. All subjects underwent history taking and physical examinations to evaluate for the presence and severity of varicocele ht,weight and BMI, those compared with 206 men without varicocele (control group)were selected randomly from general population. Results : The mean (± SD) BMI of the 206 patients with varicocele was 25.2721 While that of control group was 28.8441((P =0.0001).which is clinically significant. Varicocele grade significantly decreased with increasing BMI category (p =0.0001). Conclusions: The results of this study indicate that there is a decreasing incidence of varicocele and varicocele grade with increasing BMI. Supporting the possibility that obesity results in a decreased nutcracker effect in which the adipose tissue prevents compression of the renal vein.